KONSEP KEADILAN SOSIAL DALAM JUZ KE 3 ALQURAN: ANALISIS TAFSIR AL-MISBAH DAN TAFSIR IBN KATSIR - Ramadhan, Alfithrah; Hermanto, Edi (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to examine the concept of social justice in Juz 3 of the Qur'an through a thematic interpretation approach by analyzing two main sources, namely Tafsir Al-Misbah by M. Quraish Shihab and Tafsir Ibn Katsir by Ibn Katsir. The focus of the study is on several verses such as Al-Baqarah verses 254, 256, 282, and Ali Imran verse 92, which explicitly and implicitly contain the values ​​of social justice. The results of the analysis show that Tafsir Al-Misbah emphasizes a contextual approach and humanitarian values, so that it is more relevant in answering contemporary social issues. Meanwhile, Tafsir Ibn Katsir uses a narrative approach based on hadith and atsar, with an emphasis on the spiritual and historical aspects of justice in Islamic society. Both interpretations agree that social justice in Islam includes material, spiritual, and moral dimensions, and is realized through the protection of individual rights, fair distribution of wealth, and the elimination of social inequality. This study confirms that the understanding of social justice according to the Qur'an has a strong foundation in the holy text and classical-modern interpretations, and can be a guideline in building a just and civilized society.